Highly Safe, Durable, Adaptable, and Flexible Fuel Cell Using Gel/Sponge Composite Material. Issue 6 (29th December 2021) - Zou, Siyi; Li, Yali; Jin, Hanqing; Ning, Fandi; Xu, Pengpeng; Wen, Qinglin; Pan, Saifei; Dan, Xiong; Li, Wei; Zhou, Xiaochun
Abstract: With the rapid development of portable and wearable electronics, safety concerns over flexible energy devices are inevitable. Therefore, it is important to develop energy supplies that are safe for use. In this work, a highly safe, durable, adaptable, and flexible air‐breathing direct methanol fuel cell (DMFC) is successfully prepared by synthesizing and applying a new composite material with agar gel and wood sponge, that is, a gel/sponge composite. The gel/sponge composite has a high absorption rate, high cyclic performance, high methanol absorption capacity, high energy content, and high flexibility. Moreover, the gel/sponge composite with 1.5% agar gel retains approximately 90% of the methanol solution at a pressure of 29.4 kPa, and the areal energy density of the proposed DMFC approaches 13.7 mWh cm −2 . Both the single‐cell and stack of DMFC with the new composite material successfully survive a series of destructive tests, including needle penetration, cutting, and compression. Therefore, it is successfully demonstrated that absorbent materials can greatly boost the safety, adaptability, flexibility, and energy density of air‐breathing DMFCs. Furthermore, this concept shows promise in improving the safety of other fuel cells by using absorbent materials to solidify their gaseous or liquid fuels. Abstract : With the rapid development of portable and wearable electronics, safety concerns over flexible energy devices are inevitable. In this work, a highly safe, durable, adaptable, and flexible air‐breathing direct methanol fuel cell is successfully prepared by synthesizing and applying a new composite material with agar gel and wood sponge, that is, a gel/sponge composite.